La construction du cadre de la scolarisation comme contexte de littératie par les enseignants brésiliens - Maira Mamede (Recherches en Éducation)
Scholar difficulties, especially among students of popular origin are largely due to unfamiliarity with literacy. But, beyond these difficulties that may be rooted in the social background of students, it seems necessary to ask how the frame of schooling is constructed as a context of literacy. Our objective was to identify pedagogic modes at work in Brazilian public schools, receiving only students from disadvantaged social groups, and observe how these modes are literacy contexts, particularly from the distinction between restricted and full literacy. Our analysis of classroom observations, both in primary and secondary education, shows that scolarisation frame can promote restricted or full literacy, depending on the implementation, by teachers and by students, of cognitive potentials related to literacy (orally or written). These first results have led to questions about the insertion in literacy of teachers themselves, especially since most of Brazilian teachers come from families with little or no schooling at all. In order to determine if teachers themselves are in full literacy, we analyzed writings produced in teacher education context. Analyses show that these productions are invested from writing modalities unlikely to support the actualization of cognitive potential related with literacy. Therefore, since some teachers are restrictedly literated, it seems unlikely that they can to be able to include students in full literacy.